Activity of a melimine derived peptide Mel4 against Stenotrophomonas, Delftia, Elizabethkingia, Burkholderia and biocompatibility as a contact lens coating. Issue 3 (June 2017) - Dutta, Debarun; Zhao, Timothy; Cheah, Kai Bing; Holmlund, Larke; Willcox, Mark D.P.
Highlights: Mel4 contact lens coating retain high activity against Delftia, Stenotrophomonas, Elizabethkingia, Burkholderia . Mel4 coated antimicrobial contact lenses are biocompatible during 22 days rabbit lens wear. These lenses did not show increased redness or corneal staining during 1 week daily wear for humans. Abstract: Purpose: To determine the antimicrobial activity of the melimine derived peptide Mel4 against Delftia, Stenotrophomonas, Elizabethkingia, Burkholderia and to investigate biocompatibility of Mel4 as an antimicrobial coating on contact lenses in animals and humans. Methods: In vitro antimicrobial activity of Mel4 was determined against the four Gram negative bacteria by investigating growth curves for 24 h followed by viable counts to determine the minimum inhibitory concentration (MIC). Contact lenses were coated by covalently binding Mel4, characterized by amino acid analysis, and were investigated for changes in lens parameters. Safety of Mel-4 coated lenses were determined in a rabbit model of daily contralateral wear. A prospective, randomised, double-masked, contralateral, 1week daily wear human clinical trial was used to evaluate subjective responses and ocular physiology. Results: Mel4 was active against all the bacteria tested (MIC50 ranged from 31–1000 μg ml −1 ) and produced an antimicrobial surface on contact lenses. Mel4-coating resulted hydrophilic surface without any significant change in contact lens parameters, and showed no signs of cytotoxicity or ocular irritation during rabbit wear. During human clinical trial, there were no differences between Mel4 coated and uncoated contact lenses in lens performance indicators and ocular signs such as corneal fluorescein staining. Mel4 and control uncoated lenses had no differences in ocular symptoms during lens wear. Conclusion: Mel4 has achieved antimicrobial activity against variety of Gram negative bacteria that are often resistant to the action of cationic peptides and have been implicated in contact lens related adverse events. Mel4-coated contact lenses were safe to wear.